The educational status of the ultra poor - Halder, Shantana R. (Research and Evaluation Division, Brac, 2019)
This report describes the state of education of the ultra poor by considering four indicators namely: net enrollment rate of children between 6-10 years of age, adult and household literacy rates, educational status of the household heads and the rate of "educationally dark" or "enlightened" households. Net enrollment rate was 55%, while the rural national average was 77%. The rate was highly correlated with amount of land, quality of housing, sex, occupation and literacy status of the household heads, household asset base and saving. Increase in income enhances girls' enrollment more positively. About 51% of the households were educationally dark, where none of the family members had completed at least one year of education. The number of educationally dark households was proportionately higher among the landless, femaleheaded households and also among the destitutes. No direct relationship between this variable with household income was observed. Household literacy rate was 28%. It was about twice higher for male than female. Among the female-headed households, male literacy rate was more than four times higher compared to the female literacy rate. Similar trend was also observed for the destitutes and the most well-off. Land was found to be positively correlated with household literacy.